How can multiculturalism be celebrated through teacher training in Israel? - Shapira, Noa; Amzalag, Meital (Frontiers in Education, 2024)
Can we celebrate multiculturalism through teachers' training in a heterogeneous and diverse setting such as Israeli society? The current study examines teachers' processes through an online teachers' professional development program and an interactive activity, where 68 Israeli teachers shared their cultural stories with teachers from other cultures.Findings indicate that the teachers who met with teachers from other cultures, whom they usually don't meet, wanted to learn about each other's culture, including their religious values, practices, and traditions while looking for commonalities. Furthermore, such intercultural meetings can occur online if the activities are designed to foster meaningful meetings and discussions between different cultures despite the social rifts and the separation within the education system.